Braća R. Pijade hosiery factory - Lukić Nenad; Ćosović Olivera (Tekstilna industrija)
Based on preserved sources, the paper shows the establishment and operation of the Braća R. Pijade Hosiery Factory. This little-known factory has been in business since 1927, surviving on the domestic market and maintaining stable production despite the challenges imposed by various regulations and dictates of the cartel, made up of the largest hosiery manufacturers. Located in Belgrade and owned by Lazar Pijade, it had men's, women's and children's socks in its assortment. Although the business was burdened with various debts, it continued until the Second World War and the tragic fate of the owner's family.